Synergistic effect of co-combustion of EFB char with coal using BET analyzer: article - Naharudin, Nabilah; Ahmad, Normadyzah; Idris, Siti Shawalliah; Abd Ghani, Fazni Susila (2019)
This study is to identify the synergistic effect during co-combustion between EFB char with MB coal blends by using Brunauer-Emmett-Teller (BET) analyser. The pore specific volume and surface area of EFB char and MB coal blends were investigated over a range of different weight ratio and temperature. In this research, the weight ratio of EFB char/MB coal blends are from 100:0, 60:40, 20:80, and 0:100 and the temperature for co-combustion will be conducted at 400, 600, and 700°C. Raw EFB were pyrolyzed in microwave pyrolysis condition at 300 W exposed for 35 minutes. The resulting solid char was mixed with MB coal at different blending ratio prior undergoing co-combustion in furnace. A BET analyser was used to analyse the BET surface area of the co-combusted product. The results revealed that the surface area is inversely proportional to temperature of combustion. The higher the combustion temperature, the lower the BET surface area. Besides that, as the mass fraction of EFB char increase, the surface area of pores decreases. Overall, the actual BET surface area obtain experimentally does not synchronize with the predicted BET surface area. Therefore, there is a synergistic effect occur on the co-combustion of EFB char with MB coal.